'A Person Takes Something and Makes It Into Something Else': Lessons from Stories of Reading a Fragment. Issue 4 (2nd October 2021) - Naishtat Bornstein, Lilach
ABSTRACT: Here I present 'stories of reading' as a model that takes account of the way an actual reader, together with other readers in a group, reacts to a text as part of an interpretive event. I demonstrate the model through the shared reading and discussion, by a non-academic group of Israeli women, of a Hebrew translation of Samuel Taylor Coleridge's Romantic fragment Christabel . This work, published in 1816, has produced a rich history of 'stories of reading' in oral group discussions during its creation and since its reception. Thus, I argue, it entails collaborative investigation and interpretation. Moreover, its potential as a fragment poem may be fully uncovered and brought to the fore when read in a group context. I present an ethnography of the reading that examines how personal and collective 'stories of reading' in this group revealed meanings of the poem.